Cross-country determinants of market efficiency: A technical analysis perspective - Fang, Jiali; Jacobsen, Ben (Journal of Banking & Finance, 2024)
This study examines the relative impact of seven factors, including herding, sentiments, and institutional quality, on varying levels of weak form market efficiency across 50 stock markets. The analysis focuses on the profitability of technical analysis trading strategies to address issues with other (statistical) market efficiency measures related to information and transaction costs (Griffin et al., 2010). Proxies for herding, institutional quality, and equity market development consistently emerge as the most significant cross-country determinants of relative market efficiency. In contrast, proxies for fractionalization, chaos, and investor protection play comparatively weaker roles. We also find no clear link between market efficiency and sentiment proxies.